Investigation of chemical components and purities of eight Malaysian honeys as compared to manuka honey - Moniruzzaman, Mohammed (2015)
Introduction: Malaysia, a tropical country rich with flora and fauna has many different types of honeys. Although honey is produced and is greatly consumed in Malaysia, there is a lack of information on the chemical composition of these honeys. Thus, the present study was aimed to investigate the chemical composition (physical, chemical, antioxidant parameters, minerals, trace elements, volatile compounds and sugar content) of eight different Malaysian honeys (acacia, pineapple, gelam, longan, borneo, rubber tree, sourwood and tualang) compared to manuka honey. Methods: Different physical and antioxidant parameters were measured using spectrophotometric techniques while phenolic acid composition was determined by high performance liquid chromatography. Minerals and trace elements were determined using atomic absorption spectrometry. Gas chromatography quadrupole time-of-flight mass spectrometry (GC-QTOF-MS) was used for the first time to analyse honey volatiles and subsequently a novel dispersive liquid-liquid microextraction (DLLME) method was developed to analyse volatiles. Sugar analysis was performed by GC-MS. Results and discussions: The physical parameters of the investigated honeys were within the limit recommended by International Honey Commission. The mean concentration of phenolics (325.59 ± 168.45 mggalicacid/kg) and flavonoids (62.52 ± 56.06 mgcatechin/kg), DPPH radical scavenging activity (43.02 ± 14.03%) and ferric reducing power was 329.70 ± 209.16 μM Fe (II)/100 g. Benzoic acid was the most abundant phenolic compounds (75%) among the phenolic acids followed by caffeic acid, catechin, myricetin, gallic acid and naringenin. High mineral contents were observed in the investigated honeys with K, Na, Fe and Ca being the most abundant elements (mean 1466.01, 230.15, 133.39 and 144.48 mg/kg, respectively). Overall, the trace elements were within the recommended limits with no pesticide residues detected in any of the honey samples indicating their good qualities. Following analysis using headspace (HS) solid-phase microextraction (SPME), accurate mass capabilities of GC-QTOF-MS evaluated for compounds identification showed a relatively narrow mass window (0.005 Da). Finally, a novel DLLME method was developed and optimised to analyse honey volatiles. The whole sample preparation process was completed in only approximately 10 min, with a total consumption of organic solvents below 4 mL, relative standard deviations lower than 12% and approximately 78 organic compounds identified in the obtained extracts. Several sugars were identified and quantified in honeys. Conclusion: Sourwood, longan and tualang honeys have higher number of phenolic acids, flavonoids with superior antioxidant potentials when compared to other Malaysian honeys and manuka honey. Overall, the results of this research indicate that Malaysian honeys are of good qualities.